Phylogeny and generic limits in the sister tribes Psychotrieae and Palicoureeae (Rubiaceae): Evolution of schizocarps in Psychotria and origins of bacterial leaf nodules of the Malagasy species2. Issue 7 (1st July 2014) - Razafimandimbison, Sylvain G.; Taylor, Charlotte M.; Wikström, Niklas; Pailler, Thierry; Khodabandeh, Anbar; Bremer, Birgitta
Abstract : Premise of the study: The pantropical, species‐rich Psychotrieae and Palicoureeae are sister tribes of mostly drupe‐bearing and nonbacterial leaf‐nodulating species with problematic generic limits. This problem is more complicated in Psychotrieae due to the paraphyly of the genus Psychotria, the lack of diagnostic characters for some major lineages, and the poor sampling from some biodiversity hotspots. Schizocarps and bacterial leaf nodules have been used for recognizing formal groups in Psychotrieae, but their evolution and taxonomic value have not been studied using a robust phylogeny of the tribe. Methods: We analyzed 287 samples from the entire ranges of the tribes, with particular emphasis on the Western Indian Ocean region, with the Bayesian Markov chain Monte Carlo method. Key results: All allied Psychotria genera investigated are nested within a paraphyletic Psychotria . Schizocarps evolved independently two times within Psychotria, and one reversal back to the drupaceous condition is inferred. The Malagasy leaf‐nodulated Psychotrieae (except Apomuria bullata ) and the Comorian non‐leaf‐nodulated Psychotria conocarpa are nested within the (African) leaf‐nodulated clade. Within Palicoureeae, Chassalia is paraphyletic with respect to Geophila sensu stricto, and the Malagasy Geophila gerrardii and the African Hymenocoleus are closely related. Conclusions: A widely circumscribed Psychotria encompassing the entire Psychotrieae is supported. Within Psychotria, two separate origins of schizocarps from drupes, one reversal back to the drupaceous condition, and two independent origins of the Malagasy leaf‐nodulated species are inferred. A new genus Puffia is described to accommodate Geophila gerrardii, and a narrow circumscription of Chassalia is adopted. Thirty‐two new combinations, two lectotypifications, and 25 new names are presented.